THE BOOK OF BURKUN-DARGO. Review on the book by Kurbanov M.-Z.Y. «Burkun-Dargo. History, culture and way of life: the past and the present». - Makhachkala: Nauka-Dagestan, 2015 - Aliev, B G (History, Archeology and Ethnography of the Caucasus, 2016)
-